GE_GERICHTE P/14933/2018 vom 6. November 2018 - GE Cour de justice (2018)
VOL(DROIT PÉNAL) ; AFFILIATION À UNE BANDE ; PAR MÉTIER ; SOUPÇON ; RISQUE DE FUITE ; PROPORTIONNALITÉ | CPP.221; CP.139.ch2; CP.139.ch3